Does coffee drinking have beneficial effects on bone health of Taiwanese adults? A longitudinal study - Chang, Huan-Cheng (BMC Public Health, 2018)
BACKGROUND: Results from studies investigating the association between coffee consumption and osteoporosis or bone mineral density (BMD) have been inconsistent. This longitudinal study was performed to assess the effect of coffee drinking on bone health of Taiwanese adults. METHODS: Data were retrieved from the Li-Shin (Landseed) Hospital in Taoyuan City. In 2006, 6152 participants completed a questionnaire on coffee drinking and other lifestyle factors. In 2014, 5077 of them were followed up. Nonetheless, a total of 2395 participants with incomplete data were excluded. The final analyses included 2682 participants comprising 1195 men and 1487 women (706 premenopausal and 781 postmenopausal). T-scores were derived from the osteo-sono assessment index (OSI) which is a surrogate of BMD. Coffee drinking was categorized as “no, medium, and high” based on the number of cups that were consumed per week in both 2006 and 2014. RESULTS: In general, medium and high coffee drinking were associated with higher T-scores. However, significant results were observed only among high drinkers (β = 0.158; P = 0.0038). Nonetheless, the test for linear trend was significant (P = 0.0046). After stratification by sex, medium and high coffee drinking were associated with higher T-scores. However, significant results were prominent only among high male drinkers (β = 0.237; P = 0.0067) and the test for trend was significant (P = 0.0161). Based on menopausal status, coffee drinking was associated with higher T-scores. Nevertheless, significant results were found only among premenopausal women (β = 0.233; P = 0.0355 and β = 0.234; P = 0.0152 for medium and high coffee drinking, respectively. The test for linear trend was significant (P = 0.0108). CONCLUSION: Coffee drinking was significantly associated with higher T-scores hence, a lower risk of osteoporosis in men and premenopausal women. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12889-018-6168-0) contains supplementary material, which is available to authorized users.